2016
DOI: 10.1016/j.jag.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Timber production assessment of a plantation forest: An integrated framework with field-based inventory, multi-source remote sensing data and forest management history

Abstract: a b s t r a c tTimber production is the purpose for managing plantation forests, and its spatial and quantitative information is critical for advising management strategies. Previous studies have focused on growing stock volume (GSV), which represents the current potential of timber production, yet few studies have investigated historical process-harvested timber. This resulted in a gap in a synthetical ecosystem service assessment of timber production. In this paper, we established a Management Process-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…According to the Food and Agriculture Organization of the United Nations (FAO) [1], since 1990, tropical and subtropical regions have been experiencing particularly rapid rates of forest plantation expansion, mostly in countries in Asia and South America, by 4.3 million ha/year. Timber production is the main ecosystem service of planted forests and the main management objective for these plantations [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization of the United Nations (FAO) [1], since 1990, tropical and subtropical regions have been experiencing particularly rapid rates of forest plantation expansion, mostly in countries in Asia and South America, by 4.3 million ha/year. Timber production is the main ecosystem service of planted forests and the main management objective for these plantations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The value of remote sensing data to estimate forest parameters such as DBH, AGB, tree height and density has been demonstrated. Recent studies suggest that different combinations of satellite data, i.e., multi-frequency SAR data, optical and textural data improve forest parameters estimation [30][31][32][49][50][51][52]. Methodology and data vary greatly across these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial diversity of forest canopies makes the relationship between forest parameters and remote sensing data a major challenge, although several studies have already demonstrated correlation between spectral data and forest characteristics of interest (Stojanova et al 2010, Viana et al 2012, Castillo-Santiago et al 2013, Fayad et al 2016, Gao et al 2016. For instance, plantations comprised of different Eucalyptus species may have very similar values of basal area and volume, but have different spectral characteristics due to differences in spectral behaviour of the species that form the canopies.…”
Section: Discussionmentioning
confidence: 99%
“…Timber production is the main ecosystem service of planted forests and the main management objective for these plantations (Gao et al 2016). In the case of fastgrowing plantations, the correct determination of stand productivity is essential to support forest management planning strategies (González-García et al 2015, Retslaff et al 2015.…”
Section: Introductionmentioning
confidence: 99%